Harrison Principios de Medicina Interna - Loscalzo, Joseph; Fauci, Anthony; Kasper, Dennis; Hauser, Stephen; Longo, Dan; Jameson, J. Larry (McGraw-Hill's AccessMedicina., 2022)
This book focuses on essential information with the goal of providing clear and definitive answers to clinical questions.